DEFORMATION BEHAVIOR OF SHIRASU SOIL BY THE EXTENDED SUBLOADING SURFACE MODEL - M. Hira; K. Hashiguchi; M. Ueno; T. Okayasu (Lowland Technology International, 2006)
This study is aimed at evaluation of the deformation behavior of Shirasu soil (volcanic sandy soil) for reclamation and embankment construction, using elastoplastic constitutive equation based on the subloading surface model with the rotational hardening. Test results for isotropic consolidation and monotonic/cyclic loading-unloading compression with several lateral stresses under the drained conditions for various initial void ratios are reported. Further, the simulation by the constitutive equation based on the extended subloading surface model is compared with the test results. High applicability of the constitutive equation for the prediction of mechanical behavior of Shirasu soil for a geo-material at the lowland in the southern Kyushu is verified by the comparison.